Evoluindo comportamentos para um artefato de arte interativa baseado em cubos - Oliveira, Victor Martin de (2017)
In the context of interactive art, which the spectators become interactors as well, technological development promotes new types of interaction and relations between the art and the human. The project “C³ – Cubos Interativos” (C³ project) rises in this context, created by Media Lab -- UFG with the philosophy of interpersonal and interactive relations, using art and technology. The project consists of three real cubes, which can be handled by users and produce feedback through light and sound effects. The users may communicate with one another and interact with the cubes in order to discover their behaviors and the possible reactions to the interactive activities. However, the cubes behaviors are created manually through the codification of a state machine, being a complex and time consuming task. On the other hand, the Interactive Evolutionary Computation (IEC) is an area of research that can be applied to the composition of artistic elements by using evolutionary algorithms and human interaction. One down point of the IEC is the human fatigue, what makes prohibitive the processing of many evolutionary cycles. Some techniques can be applied to avoid this problem, for example, the use of surrogate functions. This work aims to unite aspects of interactive art and interactive evolutionary computation, with the objective of providing a new way of creating behaviors that represents interesting and pleasant compositions to the C³ cubes. To achieve this goal, we propose the evolution of the C³ cubes state machines using IEC assisted by a surrogate function. A simulation environment for the C³ project was developed, in which the users can interact with virtual cubes and evaluate their behaviors, guiding the evolutionary approach. An experiment with the approach involving a group of users from UFG resulted in more complex and interesting C³ projects.